Artropodos asociados con Guadua angustifolia almacenada en Pereira, Colombia - Saenz Aponte, A.=700 1 Montoya, J.A.; Tistl, M.
(Es, En)
Ilus., 22 ref.
Keywords: INSECTOS DAÑINOS; COLEOPTERA; HYMENOPTERA; PLAGAS DE PRODUCTOS ALMACENADOS; GUADUA ANGUSTIFOLIA; COLOMBIA; DINODERUS MINUTUS; EUCALANDRA SETULOSUS